Analysis of Lead (PB) Levels in Snack Foods at Joyoboyo Terminal, Surabaya as a Public Health Risk - Maryati, Ani; Sophearom, Chhea; Bunleang, Ky (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: Study aimed to analyze the levels of lead (Pb) in snack foods sold at Terminal Joyoboyo, Surabaya, and to assess their potential risk to public health. Methodology: An analytical observational study with a cross-sectional design was conducted. A total of 30 snack food samples were collected using purposive sampling from vendors located inside and outside the terminal. Lead levels were measured using Atomic Absorption Spectrophotometry (AAS). Data were analyzed using descriptive statistics and an independent samples t-test to determine differences between groups. Main Findings: The findings showed that all samples contained detectable levels of Pb, with higher mean levels observed in foods sold outside the terminal (0.28 mg/kg) compared to those inside (0.19 mg/kg). Approximately 40.0% of samples from outside the terminal exceeded the safety limit, compared to 13.3% from inside. Statistical analysis indicated a significant difference between the two groups (p < 0.05). Novelty/Originality of this study: This study provides a micro-spatial analysis of Pb contamination by comparing food safety conditions within different zones of the same transportation terminal, offering more precise insights into environmental exposure risks.